2003
DOI: 10.1046/j.1442-9071.2003.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for proinflammatory nature of perfluorohexyloctane in the eye

Abstract: The data do not indicate any benefit of F6H8 over other perfluorocarbons for use in short-term post-operative intraocular tamponade. Although early experience suggests that F6H8 use in primary vitrectomy with minimal PVR is acceptable and produces temporary inflammatory effects only, these cases can often be successfully managed by conventional scleral buckling techniques, or vitrectomy with standard tamponading agents, without the need for F6H8 and subsequent extra surgical procedures. Furthermore in eyes alr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 21 publications
1
54
1
4
Order By: Relevance
“…26 In a clinicopathological report, Vote et al suggested that F6H8 had a proinflammatory effect, possibly related to its tendency to disperse. 40 In addition, recent experimental studies have pointed to a possible toxic effect of F6H8 on animal and human cell cultures. 41,42 From the foregoing, it is clear that the use of FALK as internal tamponade is still a concern.…”
Section: Eyementioning
confidence: 99%
“…26 In a clinicopathological report, Vote et al suggested that F6H8 had a proinflammatory effect, possibly related to its tendency to disperse. 40 In addition, recent experimental studies have pointed to a possible toxic effect of F6H8 on animal and human cell cultures. 41,42 From the foregoing, it is clear that the use of FALK as internal tamponade is still a concern.…”
Section: Eyementioning
confidence: 99%
“…While some authors found encouraging results, 11,12 other groups reported a plethora of complications and discouraged the use of F6H8 as a vitreous substitute. [13][14][15][16] Around the same time, two new tamponades showed promising results in initial experimental settings, OL62HV and O62, only too soon to be associated with a high failure rate and massive complications. 14,17 Double filling with F6H8 and silicone oil has also been tried to provide simultaneous superior and inferior tamponade but, as both substances merged, the resulting tamponade bubble proved less effective than expected.…”
Section: Introductionmentioning
confidence: 99%
“…Para a análise quantitativa dos extratos sobre as culturas celulares utilizamos o método descrito por Murakami et al (22) . Resumidamente, 100 µl de uma suspensão de células Vero contendo 1,0 x 10 6 células/ml em meio Ham-F10 com 10% de SFB foram inoculadas em uma placa de cultura com 96 poços (Corning ® , Cambridge, MA, USA) e cultivadas por 12 h nessas condições a 37ºC.…”
Section: Análise Quantitativa Dos Extratos Sobre As Culturas Celularesunclassified
“…Estudos com o perfluorohexiloctano como substituto do vítreo em olhos de coelhos não mostrou alterações retinianas importantes na microscopia ótica e eletrônica (19) e a experiência clínica com o F 6 H 8 , embora limitada, mostra respostas distintas quanto ao dano retiniano e resposta inflamatória, conforme diferentes trabalhos (20)(21)(22) . Apesar desses achados iniciais, e devido ao fato do F 6 H 8 ser um produto novo, estudos referentes a citotoxicidade desse composto são necessá-rios para comprovar a sua segurança.…”
Section: Introductionunclassified